Effect of Modified Atmosphere, Vacuum and Polyethylene Packaging on Physicochemical and Microbial Quality of Chestnuts (Castanea sativa) during Storage - Fernandes, Luana (2018)
There is a commercial requirement to extend the shelf-life of chestnuts. This study aimed to determine the effect of different packages (modified atmosphere packaging (MAP) (0.3% O2 and 32% CO2), polyethylene (PE) and vacuum (VAC)) on physicochemical and microbial properties of raw chestnuts during storage (1, 2, 3 and 6 months). The results showed that the storage time and packaging type influence chestnuts properties. VAC and MAP showed a decrease in the aw, maximum force, and hardness values of the fruits at the end of storage. All treatments may also cause color modifications in the fruit. Total acidity and total soluble solids values remained similar between samples, although they increased in the first two months of storage. During the storage period, there was a significant increase in microorganism counts in the control and PE samples, being observed germination after one month in the latter situation. On the contrary, the use of MAP and VAC could significantly control the proliferation of the microorganisms; however, after 3 to 6 months, the chestnuts lost quality, showing a fermented smell.